The legacy of Iraq : from the 2003 War to the 'Islamic State' - Isakhan, Benjamin, 1977- (Edinburgh University Press, 2015)
Examines the complex and difficult legacies of the Iraq war of 2003 and their critical relevance today. In March 2003, a US-led 'Coalition of the Willing' launched a pre-emptive intervention against Iraq. Their ambitious project was to turn Iraq into a liberal democracy, underpinned by free-market capitalism, its citizens free to live in peace and prosperity. However, the Iraq war did not go to plan and the coalition were forced to withdraw all combat troops at the end of 2011, having failed to deliver on their promise of a democratic, peaceful and prosperous Iraq. The Legacy of Iraq critically reflects on this abject failure and argues that mistakes made by the coalition and the Iraqi political elite set a sequence of events in motion that have had devastating consequences for Iraq, the Middle East and for the rest of the world. Today, as the nation faces perhaps its greatest challenge in the wake of the devastating advance of the Islamic State of Iraq and Syria (ISIS) and another US-led coalition undertakes renewed military action in Iraq, understanding the complex and difficult legacies of the 2003 war could not be more urgent. To ignore the legacies of the Iraq war and to deny their connection to contemporary events means that vital lessons could be ignored and the same mistakes made again.